Maternal Health-Care in India: The Case of Tetanus Toxoid Vaccination - Khan, Rana Ejaz Ali; Raza, Muhammad Ali (Asian Development Policy Review, 2013)
Prenatal-care is one of the important elements of maternal health-care. In this paper an attempt has been made to examine the socioeconomic determinants of Tetanus Toxoid (TT) vaccination as a component of prenatal-care by the women in the age group of 15-49 years. Micro-data having 25847 observations from Indian Demographic and Health Survey (IDHS) has been used. To estimate the probability of TT vaccination binary logistic regression has been utilized. The explanatory variables categorized into socio-demographic characteristics of the woman, household characteristics, health-related characteristics, community characteristics and regional characteristics have been included in the analysis. The results explained that probability to have TT vaccination increases by woman’ education, woman’ age at marriage, husband’s age, husband’s education, husband’s living within household, husband’s presence at prenatal visit and household wealth. The woman’s living in small city, town and country side as well as final say on woman’s health-care by woman and husband collectively, and husband alone decrease the probability of TT vaccination. The study proposed targeted approach to enhance the TT vaccination in Indian women. The marginalized households should be targeted through cash transfer programs. Furthermore, the small cities and country sides should also be focused. The awareness and education of woman along with husband’s participation in maternal health-care cannot be ignored in policy making.